Optical glass, prefabricated member thereof, optical element and optical instrument
By optimizing the proportions of components such as SiO2, B2O3, La2O3, Y2O3, ZnO, ZrO2, Nb2O5, optical glass with refractive index and dispersion characteristics was designed, which solved the problem of thermal expansion coefficient limitation of high-refractive index optical glass in the on-board field, and achieved the Negative short-wave relative partial dispersion and low thermal expansion coefficient.
Patent Information
- Application Number
- CN202411408043.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-07
AI Technical Summary
The application of high-refractive index optical glass in the automotive field is limited by the thermal expansion coefficient, making it difficult to achieve the performance of low thermal expansion coefficient and negative short wave relative partial dispersion simultaneously.
Using the combination of components such as SiO2, B2O3, La2O3, Y2O3, ZnO, ZrO2, Nb2O5, etc., by adjusting the proportion of each component, the refractive index is designed to be 1.70-1.75, the Abbe number is 43-48, and the relative part of the short wave dispersion is Optical glass with a thermal expansion coefficient of 70×10-7/℃ or less.
It realizes optical glass with negative short-wave relative partial dispersion and low thermal expansion coefficient in high-performance optical systems, meeting the high-performance needs of the automotive field.
Smart Images

Figure CN119263628A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to optical glass, in particular to optical glass with a low thermal expansion coefficient, and a glass preform, an optical element and an optical instrument made of the optical glass. Background Art
[0002] Optical glass with high refractive index, low dispersion and negative short-wave relative partial dispersion has significant application value in optical systems such as car cameras, digital cameras, and projectors. High refractive index and low dispersion glass lenses can form relatively small optical path differences for different colors of light while achieving refraction, which is beneficial to reducing the curvature and thickness of glass lenses for chromatic aberration correction, thereby improving the overall performance of the optical system and reducing the difficulty of design. If glass with a relatively high refractive index also has a large negative short-wave relative partial dispersion, it is beneficial to eliminate secondary chromatic aberration of the optical system on the basis of a smaller total length of the optical system.
[0003] The internal lenses in the optical systems of some application scenarios of high-refractive and low-dispersion optical glass (such as vehicle-mounted cameras, security lenses, etc.) may be subject to humidity, high temperature, thermal shock, vibration, etc. due to the randomness of the use environment, which places high demands on the hardness, chemical stability, thermal expansion coefficient and other properties of the optical glass. In particular, the automotive-grade thermal shock standard poses a huge challenge to the thermal shock resistance of optical glass, limiting the application of optical glass in the automotive field. As an oxide brittle material, the maximum tensile strain and thermal conductivity of glass are not easy to change. Therefore, the key to improving the thermal shock resistance of optical glass lies mainly in reducing its thermal expansion coefficient. However, since high-refractive index optical glass often needs to be realized through a high-content high-polarizability glass network intermediate, resulting in insufficient density of the glass network, it is not easy for high-refractive index optical glass to have a low thermal expansion coefficient. Summary of the invention
[0004] Based on the above reasons, the technical problem to be solved by the present invention is to provide a short-wave relative partial dispersion (ΔP g,F ) and optical glass with low thermal expansion coefficient.
[0005] The technical solution adopted by the present invention to solve the technical problem is:
[0006] (1) An optical glass, the composition of which, expressed in weight percentage, contains: SiO 2 :3~15%; B 2 O 3 : 24~34%; La 2 O 3 :1~12%;Y 2 O 3 : 7~16%; ZnO: 20~30%; ZrO 2:3~9%; Nb 2 O 5 :1~6%;Al 2 O 3 :0~8%,of which (Al 2 O 3 +ZrO 2 ) / (Al 2 O 3 +B 2 O 3 +SiO 2 ) is 0.085~0.375.
[0007] (2) The optical glass according to item 1, wherein the composition, expressed in weight percentage, further comprises: Gd 2 O 3 :0~12%;and / or Li 2 O: 0~4%; and / or Na 2 O: 0-5%; and / or K 2 O: 0-5%; and / or MgO: 0-5%; and / or CaO: 0-5%; and / or SrO: 0-5%; and / or BaO: 0-4%; and / or Ta 2 O 5 : 0-5%; and / or WO 3 :0~3%;and / or Sb 2 O 3 :0~0.5%.
[0008] (3) An optical glass containing SiO 2 , B 2 O 3 ,La 2 O 3 , Y 2 O 3 、ZnO、ZrO 2 and Nb 2 O 5 As an essential component, its composition is expressed in weight percentage, containing 0-8% Al 2 O 3 , where (Al 2 O 3 +ZrO 2 ) / (Al 2 O 3 +B 2 O 3 +SiO 2 ) is 0.085 to 0.375, and the refractive index n of the optical glass d is 1.70~1.75, Abbe number ν d 43~48, short wave relative partial dispersion ΔPg,F The thermal expansion coefficient α is below -0.0075. 100~300℃ 70×10 -7 / ℃ below.
[0009] (4) The optical glass according to (3), wherein the composition, expressed in weight percentage, comprises: SiO 2 :3~15%;and / or B 2 O 3 : 24-34%; and / or La 2 O 3 :1~12%;and / or Y 2 O 3 : 7-16%; and / or ZnO: 20-30%; and / or ZrO 2 : 3-9%; and / or Nb 2 O 5 :1~6%;and / or Gd 2 O 3 :0~12%;and / or Li 2 O: 0~4%; and / or Na 2 O: 0-5%; and / or K 2 O: 0-5%; and / or MgO: 0-5%; and / or CaO: 0-5%; and / or SrO: 0-5%; and / or BaO: 0-4%; and / or Ta 2 O 5 : 0-5%; and / or WO 3 :0~3%;and / or Sb 2 O 3 :0~0.5%.
[0010] (5) The optical glass according to any one of (1) to (4), wherein the components thereof, expressed in weight percentage, satisfy one or more of the following seven conditions:
[0011] 1) Al 2 O 3 +B 2 O 3 +SiO 2 35-45%, preferably Al 2 O 3 +B 2 O 3 +SiO 2 36-44%, more preferably Al 2 O 3 +B 2 O 3 +SiO 2 37-43%;
[0012] 2) B 2O 3 / (SiO 2 +Al 2 O 3 ) is 1.5 to 4.0, preferably B 2 O 3 / (SiO 2 +Al 2 O 3 ) is 1.6 to 3.8, more preferably B 2 O 3 / (SiO 2 +Al 2 O 3 ) is 1.8~3.6;
[0013] 3)(Al 2 O 3 +ZrO 2 ) / (Al 2 O 3 +B 2 O 3 +SiO 2 ) is 0.100 to 0.325, preferably (Al 2 O 3 +ZrO 2 ) / (Al 2 O 3 +B 2 O 3 +SiO 2 ) is 0.125~0.300;
[0014] 4) Y 2 O 3 / (2×ZnO+B 2 O 3 ) is 0.090 to 0.210, preferably Y 2 O 3 / (2×ZnO+B 2 O 3 ) is 0.110 to 0.205, more preferably Y 2 O 3 / (2×ZnO+B 2 O 3 ) is 0.130~0.200;
[0015] 5) Gd 2 O 3 +Y 2 O 3 13-22%, preferably Gd 2 O 3 +Y 2 O 3 14 to 21%, more preferably Gd2 O 3 +Y 2 O 3 15-20%;
[0016] 6)(2×Li 2 O+SiO 2 ) / ZrO 2 0.800 to 5.0, preferably (2×Li 2 O+SiO 2 ) / ZrO 2 0.850 to 4.5, more preferably (2×Li 2 O+SiO 2 ) / ZrO 2 0.900~4.0;
[0017] 7)(Nb 2 O 5 +Ta 2 O 5 +WO 3 ) / (La 2 O 3 +ZrO 2 ) is 0.05 to 0.65, preferably (Nb 2 O 5 +Ta 2 O 5 +WO 3 ) / (La 2 O 3 +ZrO 2 ) is 0.05 to 0.55, and more preferably (Nb 2 O 5 +Ta 2 O 5 +WO 3 ) / (La 2 O 3 +ZrO 2 ) is 0.05~0.45.
[0018] (6) The optical glass according to any one of (1) to (4), wherein the composition, expressed in weight percentage, comprises: SiO 2 : 4-14%, preferably SiO 2 : 5-13%; and / or B 2 O 3 : 25-33%, preferably B 2 O 3 : 26-32%; and / or La 2 O 3 : 2-10%, preferably La 2 O 3: 3-8%; and / or Y 2 O 3 : 8-15%, preferably Y 2 O 3 : 9-14%; and / or ZnO: 21-28%, preferably ZnO: 22-26%; and / or ZrO 2 : 3.5~8.5%, preferably ZrO 2 : 4-8%; and / or Nb 2 O 5 : 1.5-5.5%, preferably Nb 2 O 5 : 2-5%; and / or Al 2 O 3 : 0.5-6%, preferably Al 2 O 3 :1~4%;and / or Gd 2 O 3 : 0.5-9%, preferably Gd 2 O 3 :1~6%;and / or Li 2 O: 0.05-3%, preferably Li 2 O: 0.1~2%; and / or Na 2 O: 0-3%, preferably Na 2 O: 0-1%; and / or K 2 O: 0-2%; and / or MgO: 0-2%; and / or CaO: 0-2%; and / or SrO: 0-2%; and / or BaO: 0-3%, preferably BaO: 0-2%; and / or Ta 2 O 5 : 0-2%; and / or WO 3 : 0-1.5%, preferably WO 3 :0.1~1%;and / or Sb 2 O 3 : 0~0.3%, preferably Sb 2 O 3 :0~0.2%.
[0019] (7) The optical glass according to any one of (1) to (4), wherein the optical glass does not contain K 2 O; and / or does not contain MgO; and / or does not contain CaO; and / or does not contain SrO; and / or does not contain Ta 2 O 5 ; and / or does not contain Bi 2 O 3 ; and / or does not contain TiO 2 ; and / or does not contain P 2 O 5 ; and / or does not contain GeO 2; and / or does not contain TeO 2 ; and / or does not contain Tl 2 O; and / or does not contain CdO; and / or does not contain As 2 O 3 ; and / or does not contain PbO; and / or does not contain Cl - ; and / or does not contain F - ; and / or does not contain S 2- .
[0020] (8) The optical glass according to any one of (1) to (4), wherein the refractive index n of the optical glass is d 1.70 to 1.75, preferably 1.71 to 1.74; Abbe number ν d It is 43 to 48, preferably 44 to 47.5.
[0021] (9) The optical glass according to any one of (1) to (4), wherein the short-wavelength dispersion P of the optical glass is g,F is less than 0.5600, preferably less than 0.5590, more preferably less than 0.5580; short-wave relative partial dispersion ΔP g,F It is -0.0075 or less, preferably -0.0080 or less, and more preferably -0.0085 or less.
[0022] (10) The optical glass according to any one of (1) to (4), wherein the λ 80 370 nm or less, preferably 365 nm or less, more preferably 360 nm or less; and / or λ 5 330nm or less, preferably 325nm or less, more preferably 320nm or less; and / or water resistance stability R W Class 1 and the water leaching resistance percentage is less than 0.04%, preferably Class 1 and the water leaching resistance percentage is below 0.03%, more preferably Class 1 and the water leaching resistance percentage is below 0.02%; and / or acid resistance stability R A 4 or more, preferably 3 or more; and / or density ρ is 4.05 g / cm 3 Below, preferably 4.00 g / cm 3 Below, more preferably 3.95g / cm 3 Below; and / or thermal expansion coefficient α -30~70℃ 60×10 -7 / ℃ or less, preferably 58×10 -7 / °C or less, more preferably 56×10 -7 / ℃ or below; and / or thermal expansion coefficient α 100~300℃ 70×10 -7 / ℃ or less, preferably 67×10 -7 / °C or less, more preferably 64×10 -7 / ℃ or below; and / or micro Vickers hardness H v 670×10 7 Pa or more, preferably 690×10 7 Pa or more, more preferably 710×10 7 Pa or above; and / or transition temperature T g The temperature is 540-630°C, preferably 550-620°C, more preferably 560-610°C; and / or the anti-thermal forming crystallization performance is 3 or more, preferably 2 or more, more preferably 1; and / or the anti-crystallization performance is 3 or more, preferably 2 or more; and / or the bubble degree is A 0 Grade A or above, preferably A 00 and / or a refining temperature of 1260°C or less, preferably 1240°C or less, more preferably 1220°C or less.
[0023] (11) A glass preform made of the optical glass described in any one of (1) to (10).
[0024] (12) An optical element made of the optical glass described in any one of (1) to (10) or the glass preform described in (11).
[0025] (13) An optical instrument comprising the optical glass described in any one of (1) to (10), or the optical element described in (12).
[0026] The beneficial effect of the present invention is that through reasonable component design, the optical glass obtained by the present invention has a negative short-wave relative partial dispersion (ΔP g,F ) and a low thermal expansion coefficient, meeting the requirements for high-performance optical system applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is the test result of the thermal expansion coefficient in the range of 100-300° C. of the optical glass embodiment 10 of the present invention and its polynomial fitting curve diagram. DETAILED DESCRIPTION
[0028] Below, the embodiments of the optical glass of the present invention are described in detail, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of descriptions of the repeated descriptions, the main purpose of the invention will not be limited thereby. In the following content, the optical glass of the present invention can be referred to as glass.
[0029] [Optical glass]
[0030] The following is an explanation of the range of each component of the optical glass of the present invention. In this specification, unless otherwise specified, the content, total content, and total content of each component are all expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when the oxides, composite salts, hydroxides, etc. used as raw materials for the optical glass components of the present invention decompose and transform into oxides during melting, the total amount of the oxide material is taken as 100%.
[0031] Unless otherwise indicated in specific circumstances, the numerical ranges listed herein include upper and lower limits, "above" and "below" include the endpoints, and all integers and fractions included in the range, without being limited to the specific values listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0032] The "short-wave relative partial dispersion" referred to in this article refers to the deviation of the short-wave dispersion of glass from the normal curve of optical glass. The "increase of short-wave relative partial dispersion" or "improvement of short-wave relative partial dispersion" referred to in this article refers to the increase or improvement of the difference between the short-wave relative partial dispersion value and zero.
[0033] <Essential Components and Optional Components>
[0034] B 2 O 3 It is an essential component of the optical glass of the present invention. 2 O 3 Can form [BO 3 ]、[BO 4 ]Two glass network structures, among which [BO 3 ] structure has a shorter wavelength of ultraviolet absorption peak, [BO 3 ] structure is the main source of negative short-wave relative partial dispersion properties. 2 O 3 The increase in the content of B is beneficial to the optimization of the anti-crystallization performance of the glass of the present invention. 2 O 3 Glass with more La as the main network former can 2 O 3 , Y 2 O 3 , Gd 2 O 3 , ZnO components to maintain good crystallization performance. 2 O 3 When the content of B is within a certain range, it is easy to achieve the short-wave relative partial dispersion performance of the glass of the present invention. 2 O 3If the content is too high, in order to achieve the glass refractive index within the required range of the glass of the present invention, it will inevitably lead to Nb 2 O 5 、 2 O 5 The content of high-cost components such as B increases, which increases the cost of glass. 2 O 3 The content of is 24 to 34%, preferably 25 to 33%, and more preferably 26 to 32%.
[0035] ZnO is an essential component of the optical glass of the present invention. ZnO is beneficial to improving the anti-crystallization performance and anti-thermal forming crystallization performance of the glass. An increase in the ZnO content is beneficial to improving the negative short-wave relative partial dispersion of the glass of the present invention. However, too high a ZnO content will make it difficult for the glass of the present invention to have a high refractive index while ensuring good anti-crystallization performance and a high Abbe number. Therefore, the ZnO content is 20-30%, preferably 21-28%, and more preferably 22-26%.
[0036] SiO 2 It is an essential component of the glass of the present invention. SiO 2 It can improve the devitrification resistance and thermal stability of glass. However, SiO 2 If the content is too high, the high-temperature viscosity of the glass will be too high, resulting in an increase in the glass clarification temperature and a deterioration in the melting properties of the glass raw materials. 2 The content of is 3 to 15%, preferably 4 to 14%, and more preferably 5 to 13%.
[0037] Al 2 O 3 The network structures that can be formed in glass include [AlO 4 ]、[AlO 6 ], where [AlO 4 ] is negatively charged and is usually formed in the presence of free oxygen. 2 O 3 It can consume the free oxygen in the glass and make B 2 O 3 Formation [BO 3 ] structure, thereby blueshifting the characteristic ultraviolet absorption wavelength of the glass and reducing the short-wave relative partial dispersion of the glass. The inventors have found through a large number of experimental studies that Al 2 O 3 The increase of Al content can significantly reduce the short-wave relative partial dispersion of glass. 2 O 3The increase in Al content is beneficial to improving the connectivity of the glass network when the content of glass network intermediates is high, which is beneficial to reducing the thermal expansion coefficient of the glass, increasing the Vickers hardness, and achieving a higher refractive index when the glass density is low. 2 O 3 If the content of Al is too high, the glass's resistance to thermal forming and crystallization will decrease. 2 O 3 The content is 0 to 8%, preferably 0.5 to 6%, and more preferably 1 to 4%.
[0038] The inventors have found through a large number of experimental studies that Al in glass 2 O 3 , B 2 O 3 、SiO 2 Total content of Al 2 O 3 +B 2 O 3 +SiO 2 Too high or too low will result in a decrease in the negative short-wave relative partial dispersion of the glass. Therefore, in some embodiments, Al 2 O 3 +B 2 O 3 +SiO 2 35-45%, more preferably Al 2 O 3 +B 2 O 3 +SiO 2 36 to 44%, more preferably Al 2 O 3 +B 2 O 3 +SiO 2 The Al 2 O 3 +B 2 O 3 +SiO 2 When the content is within the above preferred range, it is easy to achieve a larger negative short-wave relative partial dispersion.
[0039] The inventors have found through a large number of experimental studies that B 2 O 3 The content of SiO 2 、Al 2 O 3 Total content of SiO 2 +Al 2 O 3 The ratio B 2 O 3 / (SiO2 +Al 2 O 3 ) has a significant impact on the production performance of glass. 2 O 3 / (SiO 2 +Al 2 O 3 ) is too large, the glass evaporates a lot during the clarification and homogenization process, and too much volatiles are deposited on the top of the furnace and randomly fall into the glass liquid, which is not conducive to maintaining the consistency of the glass refractive index; B 2 O 3 / (SiO 2 +Al 2 O 3 ) is too small, the surface tension of the glass liquid is too large, the available clarification temperature is too high, and the glass evaporates a large amount during the clarification and homogenization process, which is not conducive to maintaining the consistency of the glass refractive index. Therefore, B is preferred 2 O 3 / (SiO 2 +Al 2 O 3 ) is 1.5 to 4.0, more preferably B 2 O 3 / (SiO 2 +Al 2 O 3 ) is 1.6 to 3.8, and B is more preferably 2 O 3 / (SiO 2 +Al 2 O 3 ) is 1.8 to 3.6. Within the above preferred range, the glass has a suitable viscosity and good anti-crystallization performance.
[0040] ZrO 2 It is an essential component of the glass of the present invention. ZrO 2 It can improve the hardness, refractive index and chemical stability of optical glass and reduce the thermal expansion coefficient of glass. 2 As the content of ZrO increases, the unevenness of the glass batch material during melting becomes obvious, which makes it more difficult to produce optical glass with high uniformity. 2 The further increase of ZrO content will cause the glass to require higher temperature to achieve homogenization, which will affect the life of refractory materials or platinum utensils. 2 If the content is further increased, Zr-rich paste-like precipitates are likely to appear in the glass, and the process difficulty increases sharply, making it difficult to obtain high-quality optical glass. 2 The content is 3 to 9%, preferably 3.5 to 8.5%, and more preferably 4 to 8%.
[0041] The inventor has found through a large number of experimental studies that if (Al 2 O 3 +ZrO 2 ) / (Al 2 O 3 +B 2 O 3 +SiO 2 ) is too high, the anti-crystallization performance of the glass will deteriorate, which may easily lead to quality problems such as the presence of tiny crystallization particles in the glass; if (Al 2 O 3 +ZrO 2 ) / (Al 2 O 3 +B 2 O 3 +SiO 2 ) is too low, the short-wave relative partial dispersion of the glass is difficult to reach the desired value. 2 O 3 +ZrO 2 ) / (Al 2 O 3 +B 2 O 3 +SiO 2 ) is 0.085 to 0.375, and more preferably (Al 2 O 3 +ZrO 2 ) / (Al 2 O 3 +B 2 O 3 +SiO 2 ) is 0.100 to 0.325, and more preferably 0.125 to 0.300. (Al 2 O 3 +ZrO 2 ) / (Al 2 O 3 +B 2 O 3 +SiO 2 ) Within the above preferred range, the glass has good anti-crystallization performance and desired short-wave relative partial dispersion, as well as a lower thermal expansion coefficient and a higher Vickers hardness.
[0042] Y 2 O 3 It is an essential component of the glass of the present invention. 2 O 3 The higher the content of Y, the easier it is to achieve high refractive index and low dispersion performance. 2 O 3 It can also improve the elastic modulus of glass; 2 O3 When the content is within a certain range, the thermal expansion coefficient of the glass tends to decrease. Among the components that can achieve high refractive index and low dispersion, Y 2 O 3 The cost is relatively low. However, Y 2 O 3 If the content is too high, the anti-crystallization performance of the glass will be seriously deteriorated. 2 O 3 The content of is 7 to 16%, preferably 8 to 15%, and more preferably 9 to 14%.
[0043] In some embodiments, by controlling Y 2 O 3 / (2×ZnO+B 2 O 3 ) is within a certain range, while ensuring that the optical properties of the glass reach the target value of the present invention, the glass has good anti-crystallization performance. In some embodiments, if Y 2 O 3 / (2×ZnO+B 2 O 3 ) is low. In order to realize the characteristics of the glass of the present invention, it is necessary to increase the Gd 2 O 3 The content of Gd 2 O 3 It is a precious oxide component with a high content of Gd 2 O 3 Will lead to higher glass cost, Y 2 O 3 / (2×ZnO+B 2 O 3 ) is too low, the optical properties of the glass are difficult to reach the target value of the present invention; if Y 2 O 3 / (2×ZnO+B 2 O 3 ) is too high, the anti-crystallization performance of the glass is difficult to meet the production requirements. Therefore, it is preferred that Y 2 O 3 / (2×ZnO+B 2 O 3 ) is 0.090 to 0.210, and more preferably Y 2 O 3 / (2×ZnO+B 2 O 3 ) is 0.110 to 0.205, and Y 2 O 3 / (2×ZnO+B 2 O 3 ) is 0.130 to 0.200. On the other hand, Y 2 O 3 / (2×ZnO+B 2 O 3 ) is within the above preferred range, which is also beneficial for the glass transition temperature of the glass to be within an appropriate range.
[0044] The glass of the present invention contains an appropriate amount of Gd 2 O 3 It is beneficial to improve the anti-crystallization performance of glass. 2 O 3 If the content is too high, the surface crystallization tendency of the glass will increase. 2 O 3 It is a relatively expensive component. When its content is high, the cost of raw materials for glass increases. 2 O 3 The content of is 0 to 12%, preferably 0.5 to 9%, and more preferably 1 to 6%.
[0045] G 2 O 3 and Y 2 O 3 It plays a key role in whether the optical glass can achieve the desired optical properties of relatively high refractive index and relatively large Abbe number in the present invention. 2 O 3 +Y 2 O 3 If Gd is too low, it is difficult to achieve the relatively high refractive index and relatively large Abbe number desired by the present invention; however, if Gd 2 O 3 +Y 2 O 3 If the content of Gd is too high, the glass will not be able to maintain the excellent anti-crystallization performance. 2 O 3 +Y 2 O 3 13 to 22%, more preferably Gd 2 O 3 +Y 2 O 3 14 to 21%, more preferably Gd 2 O 3 +Y 2 O 3 On the other hand, Gd 2 O 3 +Y 2 O 3 In the above preferred range, the density of the glass is relatively low.
[0046] La 2 O 3 It is an essential component of the glass of the present invention. 2 O 3It can increase the refractive index of glass, and La 2 O 3 The cost of raw materials is relatively low, so try to increase La 2 O 3 The content is beneficial to improving the cost performance of high refractive index optical glass. 2 O 3 , La 2 O 3 The increase of La content is less likely to lead to deterioration of the anti-crystallization performance of the glass. 2 O 3 Too high a content is not conducive to achieving the short-wave relative partial dispersion properties of the glass of the present invention. 2 O 3 The content of is 1 to 12%, preferably 2 to 10%, and more preferably 3 to 8%.
[0047] Nb 2 O 5 It can improve the refractive index and dispersion of glass and is an essential component of the glass of the present invention. 2 O 5 It is a high field strength component, which is beneficial to B in glass 2 O 3 With [BO 3 ] coordination structure exists, containing an appropriate amount of Nb 2 O 5 It is beneficial to increase the B content in glass under the condition of constant refractive index. 2 O 3 However, Nb 2 O 5 Too high a content of Nb will increase the cost of optical glass raw materials and will not be conducive to obtaining lower dispersion of the glass. 2 O 5 The content of is 1 to 6%, preferably 1.5 to 5.5%, and more preferably 2 to 5%.
[0048] The inventors have found through research that the glass of the present invention contains Li 2 O, the anti-crystallization performance of the glass, especially the anti-ZrO 2 The ability of crystal precipitation is significantly improved. However, Li 2 The increase of O content will lead to the decrease of chemical stability and hardness of glass. 2 The O content within a certain range does not affect the thermal expansion coefficient of the glass of the present invention. 2 When the O content is too high, the optical properties of the glass, such as the refractive index, Abbe number, and short-wave relative partial dispersion, are difficult to reach the design values of the present invention. 2 The content of O is 0 to 4%, preferably 0.05 to 3%, and more preferably 0.1 to 2%.
[0049] The inventors have found through a large number of experimental studies that when ZrO 2 As raw material, the glass contains ZrO 2 When, in the glass of the present invention, ZrO 2 Only with Li 2 O、SiO 2 Solid phase reaction occurs. 2 The chemical properties are stable. This solid phase reaction is very effective for ZrO 2 The process of raw material synthesis is very meaningful. Further, the inventors found that if (2×Li 2 O+SiO 2 ) / ZrO 2 If the value is too small, the vitrification speed will be slow and residual ZrO will be easily present. 2 Infusible substances lead to the deterioration of the internal quality of the glass, and on the other hand, the anti-crystallization performance of the glass decreases. 2 O+SiO 2 ) / ZrO 2 If the value is too large, the chemical stability of the glass will be poor and the short-wave relative dispersion will be small. Therefore, in the present invention, (2×Li 2 O+SiO 2 ) / ZrO 2 0.800 to 5.0, more preferably (2×Li 2 O+SiO 2 ) / ZrO 2 is 0.850 to 4.5, and more preferably (2×Li 2 O+SiO 2 ) / ZrO 2 It is 0.900~4.0.
[0050] Na 2 O is an optional component of the glass of the present invention. 2 O can reduce the melting temperature and refining temperature of the glass. However, in the glass of the present invention, the use of Na 2 O is likely to cause the glass to deteriorate in its resistance to thermal forming and crystallization. 2 The content of O is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%.
[0051] K 2 O is an optional component of the glass of the present invention. 2 O helps to lower the clarification temperature of the glass and increase the melting rate. However, in the glass of the present invention, K 2 The increase of O content will cause a significant decrease in the anti-crystallization performance of the glass. 2 The content of O is 0 to 5%, preferably 0 to 2%, and more preferably no K2 O.
[0052] MgO is an optional component of the glass of the present invention. MgO is beneficial to improving the chemical stability of the glass. However, too high a MgO content is not conducive to obtaining the desired optical properties of the glass of the present invention, and also leads to the deterioration of the anti-crystallization performance of the glass. Therefore, the content of MgO is 0 to 5%, preferably 0 to 2%, and more preferably no MgO is contained.
[0053] CaO is an optional component of the glass of the present invention. CaO is beneficial to improving the chromaticity and mechanical properties of the glass, but a high content of CaO is not conducive to obtaining the desired optical properties of the glass of the present invention. Therefore, the content of CaO is 0 to 5%, preferably 0 to 2%, and more preferably no CaO is contained.
[0054] SrO is an optional component of the glass of the present invention. The role of SrO in glass is similar to that of MgO and CaO. The appropriate content of SrO does not affect the anti-devitrification performance of the glass. However, a high content of SrO is not conducive to obtaining the desired optical properties of the glass of the present invention. Therefore, the content of SrO is 0 to 5%, preferably 0 to 2%, and more preferably no SrO is contained.
[0055] BaO is an optional component of the glass of the present invention. BaO has the function of increasing the refractive index of the glass, and a small amount of BaO does not affect the anti-devitrification performance of the glass. However, when the BaO content is too high, the melting process of the glass raw materials becomes difficult, and a higher melting temperature is required, resulting in a deterioration of the internal transparency of the glass. Therefore, the content of BaO is 0 to 4%, preferably 0 to 3%, and more preferably 0 to 2%.
[0056] Ta 2 O 5 It is an optional component of the glass of the present invention. 2 O 5 It can increase the refractive index of glass, but its raw materials are expensive, and high content is not conducive to reducing the cost of glass. 2 O 5 The content of Ta is 0 to 5%, preferably 0 to 2%, and more preferably no Ta is contained. 2 O 5 .
[0057] In the present invention, 0 to 3% WO 3 , which can make the glass have the desired refractive index while also having excellent anti-crystallization performance and bubble degree. 3 The content is 0 to 3%, preferably 0 to 1.5%, and more preferably 0.1 to 1%.
[0058] Nb 2 O 5 、 2 O5 , WO 3 The components are expensive and of low abundance in the earth's crust. From the perspective of reducing the use of high-cost raw materials and reducing the environmental pressure of glass production, the content of the above three components should be reduced. However, in order to achieve the excellent performance of the glass of the present invention, the inventors have found through a large number of experimental studies that (Nb 2 O 5 +Ta 2 O 5 +WO 3 ) / (La 2 O 3 +ZrO 2 ) is controlled within the range of 0.05 to 0.65, which can ensure the glass optical constants while making the glass have excellent bubble degree and thermal expansion coefficient. 2 O 5 +Ta 2 O 5 +WO 3 ) / (La 2 O 3 +ZrO 2 ) is 0.05 to 0.65, and more preferably (Nb 2 O 5 +Ta 2 O 5 +WO 3 ) / (La 2 O 3 +ZrO 2 ) is 0.05 to 0.55, and more preferably (Nb 2 O 5 +Ta 2 O 5 +WO 3 ) / (La 2 O 3 +ZrO 2 ) is 0.05~0.45.
[0059] Sb 2 O 3 As a clarifier in glass, it has the effect of increasing the bubble degree of glass. However, Sb 2 O 3 This will result in a significant decrease in the short-wave relative partial dispersion of the glass, making it difficult for the glass of the present invention to have a large negative short-wave relative partial dispersion. 2 O 3 In the case of Sb, the glass of the present invention can still have a good clarification effect due to its low viscosity. 2 O 3The content range is 0 to 0.5%, preferably 0 to 0.3%, and more preferably 0 to 0.2%.
[0060] <Ingredients not contained>
[0061] Bi 2 O 3 is a high refractive index component, but Bi 2 O 3 In glass, it has the property of significantly reducing the short-wave relative partial dispersion of glass, and Bi 2 O 3 The presence of Bi increases the difficulty of glass processing. Therefore, the glass of the present invention preferably does not contain Bi. 2 O 3 .
[0062] TiO 2 It is a high refractive index and high dispersion component, containing an appropriate amount of TiO 2 It helps to improve the anti-crystallization performance of glass. However, TiO 2 The presence of TiO significantly makes the short-wave relative partial dispersion of the glass have a positive tendency. Therefore, the glass of the present invention preferably does not contain TiO 2 .
[0063] P 2 O 5 It is a glass network former component. Although P 2 O 5 It has the effect of lowering the melting temperature of glass and increasing the ultraviolet transmittance of glass, but the glass contains P 2 O 5 This will significantly lead to a positive tendency of the short-wave relative partial dispersion of the glass. Therefore, it is preferred that the glass of the present invention does not contain P 2 O 5 .
[0064] GeO 2 、TeO 2 It is an expensive raw material. In some embodiments, it is preferred not to contain GeO 2 and / or does not contain TeO 2 .
[0065] The glass of the present invention preferably does not contain S 2- , and / or does not contain Cl - , and / or does not contain F - However, S 2- , Cl - 、F - The possibility of existing in glass in the form of impurities, fining agent residues, etc.
[0066] In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo are contained alone or in combination in small amounts, the glass will be colored and absorption will occur at specific wavelengths in the visible light region, thereby weakening the property of the present invention of improving the visible light transmittance. Therefore, it is preferably substantially free of oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, especially for optical glasses that require transmittance at wavelengths in the visible light region.
[0067] The oxides of Th, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except for being inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can be manufactured, processed and discarded.
[0068] In order to achieve environmental friendliness, the optical glass of the present invention preferably does not contain Tl 2 O, CdO, As 2 O 3 and PbO.
[0069] The "does not contain" and "0%" recorded in this article means that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be some impurities or components that are not intentionally added, and due to environmental dust impurities, etc., they will be contained in small amounts or traces in the final optical glass, and this situation is also within the scope of protection of the patent of this invention. In general, the content of the components referred to as "does not contain" and "0%" in this article in the actual glass is less than 20ppm.
[0070] Next, the properties of the optical glass of the present invention will be described.
[0071] <Refractive Index and Abbe Number>
[0072] The refractive index of optical glass (n d ) and the Abbe number (ν d ) Tested according to the method specified in the Chinese standard GB / T 7962.1-2010. d 、n F 、n C 、n g The refractive index of glass at wavelengths of 587.6nm, 480.0nm, 656.3nm, and 404.7nm respectively. d ) is defined as follows:
[0073]
[0074] In some embodiments, the refractive index (n d ) is 1.70 to 1.75, preferably 1.71 to 1.74.
[0075] In some embodiments, the Abbe number (ν d ) is 43 to 48, preferably 44 to 47.5.
[0076] <Shortwave Partial Dispersion and Shortwave Relative Partial Dispersion>
[0077] Short-wave partial dispersion (P g,F ) is defined as follows:
[0078]
[0079] Short-wave relative partial dispersion (ΔP g,F ) is defined as follows:
[0080] ΔP g,F =P g,F -0.6457+0.001703×v d
[0081] In some embodiments, the short-wave partial dispersion (P g,F ) is 0.5600 or less, preferably 0.5590 or less, and more preferably 0.5580 or less.
[0082] In some embodiments, the short-wave relative partial dispersion (ΔPg, F ) is -0.0075 or less, preferably -0.0080 or less, and more preferably -0.0085 or less.
[0083] <Internal Transparencyλ 80 and λ 5 >
[0084] The internal transmittance of glass is tested using the method described in the Chinese standard GB / T 7962.12-2010. The wavelength corresponding to the internal transmittance of a 10mm thick glass sample of 80% is defined as the internal transmittance λ 80 , the wavelength corresponding to the internal transmittance of 5% in a 10mm thick glass sample is the internal transmittance λ 5 .
[0085] Glass Lambda 80 , 5The smaller the value, the higher the transmittance of the glass to short-wave visible light, the lower the degree of color cast of the glass under visible light, and the better the use effect in the occasions of common imaging and lighting. The glass of the present invention has good internal color transmittance.
[0086] In some embodiments, the color transmittance λ of the glass of the present invention is 80 The wavelength is 370 nm or less, preferably 365 nm or less, and more preferably 360 nm or less.
[0087] In some embodiments, the color transmittance λ of the glass of the present invention is 5 The wavelength is 330 nm or less, preferably 325 nm or less, and more preferably 320 nm or less.
[0088] <Water resistance stability>
[0089] The powder method described in the Chinese standard GB / T 17129 was used to test the percentage of glass leaching under water. The glass water resistance stability (R W ) are divided into 6 categories.
[0090] Table 1.
[0091]
[0092] The glass of the present invention has good water resistance stability. In some embodiments, the water resistance stability (R W ) is Class 1 and the water leaching resistance percentage is less than 0.04%, preferably the water resistance stability (R W ) is Class 1 and the water leaching resistance percentage is below 0.03%, and the water resistance stability (R W ) is Class 1 and the water leaching resistance percentage is less than 0.02%.
[0093] <Acid resistance stability>
[0094] The powder method described in the Chinese standard GB / T 17129 was used to test the percentage of glass leaching under the action of acid. The acid resistance stability of the glass (R A ) are divided into 6 categories.
[0095] Table 2.
[0096] category Category 1 Category 2 Category 3 Category 4 5 categories 6 categories Leaching percentage <0.20% 0.20-0.35% 0.35-0.65% 0.65-1.20% 1.20-2.20% >2.20%
[0097] In some embodiments, the acid resistance stability of the glass of the present invention is Class 4 or above, preferably Class 3 or above.
[0098] <density>
[0099] The density (ρ) of optical glass is tested according to the method specified in the Chinese standard GB / T7962.20-2010. Generally speaking, the lower the density of optical glass with the same optical properties, the more it is conducive to reducing the weight of the optical system, and is beneficial to its wearable and mechanical transmission performance.
[0100] In some embodiments, the density (ρ) of the optical glass of the present invention is 4.05 g / cm 3 Below, preferably 4.00 g / cm 3 Below, more preferably 3.95g / cm 3 the following.
[0101] <Coefficient of Thermal Expansion>
[0102] The thermal expansion coefficient of glass is tested according to the method specified in the Chinese standard "GB / T 7962.16-2010". The thermal expansion coefficient of glass mentioned in this specification is the average thermal expansion coefficient of glass in the range of -30 to 70°C and in the range of 100 to 300°C, respectively denoted as α -30~70℃ and α 100~300℃ Among them, the average thermal expansion data of -30 to 70°C is closer to the conventional use temperature of optical glass and has reference significance for application; the thermal expansion meter works stably in the range of 100 to 300°C, and the data is highly accurate, which is more suitable for comparing the thermal expansion coefficients of different glasses. In general, the lower the thermal expansion coefficient of glass, the more conducive it is for the optical element and / or optical system to resist thermal shock, improve the usable temperature range, and have better use effect.
[0103] In some embodiments, the thermal expansion coefficient (α -30~70℃ ) is 60×10 -7 / ℃ or less, preferably 58×10 -7 / °C or less, more preferably 56×10 -7 / ℃ below.
[0104] In some embodiments, the thermal expansion coefficient (α 100~300℃ ) is 70×10 -7 / ℃ or less, preferably 67×10 -7 / °C or less, more preferably 64×10 -7 / ℃ below.
[0105] <Micro Vickers Hardness>
[0106] The following method is used to test the micro Vickers hardness (H v ):
[0107] First, the glass sample was precision annealed at a holding temperature of 560°C for 20 hours. After the insulation was completed, the glass sample was cooled to 440°C at a cooling rate of -4°C / h, and then cooled to room temperature at a cooling rate not higher than -50°C / h. The glass was processed into a large-surface polished sample of 40×30×10mm in size and tested using a microhardness tester. The indenter was a four-sided pyramid Vickers hardness standard indenter with a vertex angle of 135°. The applied force of the test was 2N, and the force was maintained for 10s. The relationship between the test conditions and the Vickers hardness indentation is established by the following formula:
[0108]
[0109] Where F is the test force and d is the average length of the two diagonal lines of the cross indentation.
[0110] Repeat the test 9 times and take the average value as the H of the glass sample. V . Glass H V The bigger it is, the stronger its ability to resist friction and scratches is, and the better its use value is.
[0111] In some embodiments, the micro Vickers hardness (H v ) is 670×10 7 Pa or more, preferably 690×10 7 Pa or more, more preferably 710×10 7 Pa or above.
[0112] <Transition Temperature>
[0113] Transition temperature (T g ) Tested according to the method specified in the Chinese standard "GB / T 7962.16-2010".
[0114] In some embodiments, the transition temperature (T g ) is 540 to 630°C, preferably 550 to 620°C, more preferably 560 to 610°C.
[0115] <Anti-thermal forming devitrification performance>
[0116] The anti-thermal forming crystallization performance described in this specification refers to the ability of glass to resist crystallization during the secondary thermal forming process. The test method is: cut the glass to be tested into samples of 20×20×10mm, place them in a muffle furnace kept at 780℃, take them out after a certain period of time, and observe with the naked eye and / or with a microscope whether there are crystallization particles inside the glass under the irradiation of a laser pen. According to the classification method shown in Table 3 below, the anti-thermal forming crystallization performance of glass is divided into 5 categories:
[0117] Table 3.
[0118]
[0119]
[0120] The glass of the present invention has good anti-thermal forming crystallization performance. In some embodiments, the anti-thermal forming crystallization performance of the glass of the present invention is 3 or more, preferably 2 or more, preferably 1.
[0121] <Anti-crystallization performance>
[0122] The anti-crystallization performance described in this specification characterizes the difficulty of crystal precipitation in the glass during the preparation of glass by the melting method. The stronger the anti-crystallization performance, the less likely it is to crystallize during the preparation of the glass, and the more suitable it is for industrial production.
[0123] The anti-crystallization performance of the glass of the present invention is determined by the thermal insulation method of a gradient temperature furnace. Glass without inherent defects is placed in a gradient temperature furnace with a temperature distribution in the range of 900 to 1300°C. After insulation for 4 hours, it is taken out and the junction between the crystallization area and the non-crystallization area of the glass is observed. The temperature of the gradient temperature furnace at the junction is recorded. According to the temperature value, the anti-crystallization performance of the glass is divided into 5 categories as shown in Table 4 below:
[0124] Table 4.
[0125] Classification criteria describe Category 1 Interface temperature <1100℃ Category 2 The junction temperature is 1100-1150℃ Category 3 The junction temperature is 1150-1200℃ Category 4 The junction temperature is 1200-1250℃ 5 categories Interface temperature>1250℃
[0126] In some embodiments, the anti-crystallization performance of the glass of the present invention is Class 3 or above, preferably Class 2 or above.
[0127] <Clarifying temperature>
[0128] The temperature corresponding to the glass viscosity of 100 Poise is defined as the glass clarification temperature. A low glass clarification temperature is beneficial to reducing energy consumption during the glass production process, reducing the erosion of refractory materials and platinum, and has more economic value.
[0129] In some embodiments, the clearing temperature of the glass of the present invention is 1260°C or lower, preferably 1240°C or lower, and more preferably 1220°C or lower.
[0130] <Bubble Degree>
[0131] The bubble degree of glass is tested according to the method specified in the Chinese standard "GB / T 7962.8-2010".
[0132] In some embodiments, the bubble degree of the glass of the present invention is A 0 Grade A or above, preferably A 00 class.
[0133] [Method for producing optical glass]
[0134] The optical glass of the present invention can be prepared by a conventional melting method. Specifically, oxides, hydroxides, fluorides, hydrates, various salts (carbonates, nitrates, sulfates, phosphates, metaphosphates), boric acid, etc. are used as raw materials, fully mixed according to a set ratio, and then put into a chamber composed of platinum or refractory materials at a set temperature. After a certain period of stirring, bubbling, and standing, the above raw materials undergo a solid phase reaction, melting, and homogenization process to form a uniform glass liquid. Afterwards, the glass of the present invention can be formed into any usable shape by single crucible casting and / or leaking molding.
[0135] The glass of the present invention has good glass forming properties, and those skilled in the art can obtain the preferred production process of the glass of the present invention after limited experiments. In some embodiments, the process temperature of the glass of the present invention is 1100-1300°C, preferably 1125-1275°C, and more preferably 1150-1250°C.
[0136] [Glass preforms and optical components]
[0137] A glass preform can be made from the produced optical glass by means of grinding, or by means of compression molding such as re-hot pressing, precision stamping, etc. That is, a glass preform can be made by mechanical processing such as grinding and polishing the optical glass, or by making a preform for compression molding from the optical glass, re-hot pressing the preform and then grinding the preform to make a glass preform, or by precision stamping the preform made by grinding. It should be noted that the means for preparing the glass preform are not limited to the above means.
[0138] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferred to form a preform from the optical glass of the present invention, and use the preform to perform re-hot pressing, precision stamping, etc. to make optical elements such as lenses and prisms. The glass of the present invention can also be manufactured by a one-time drop molding method.
[0139] The glass preform and the optical element of the present invention are both formed of the optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass; the optical element of the present invention has the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value. Examples of lenses include various lenses such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses, which have spherical or aspherical lens surfaces.
[0140] [Optical instruments]
[0141] The optical glass or optical element formed by the optical glass of the present invention can be used to make optical instruments such as photographic equipment, video equipment, display equipment and monitoring equipment. The optical glass or optical element of the present invention is suitable for vehicle-mounted lighting instruments, optical equipment, and is applied to the fields of vehicle-mounted and the like. The optical glass or optical element of the present invention is suitable for optical instruments such as micro-projection, micro-imaging (video / photography), and micro-illumination.
[0142] Example
[0143] <Optical Glass Example>
[0144] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided.
[0145] This embodiment adopts the above optical glass manufacturing method to obtain optical glasses having the compositions shown in Tables 5 to 8. In addition, the properties of each glass are measured by the testing method described in the present invention, and the measurement results are shown in Tables 5 to 8.
[0146] Table 5.
[0147]
[0148]
[0149] Table 6.
[0150]
[0151]
[0152] Table 7.
[0153]
[0154]
[0155] Table 8.
[0156]
[0157]
[0158] <Glass Preform Example>
[0159] The glasses obtained from optical glass embodiments 1 to 24 are used, for example, by grinding processing, or by molding methods such as hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.
[0160] <Optical Element Embodiment>
[0161] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the deformation inside the glass and perform fine adjustments so that the optical properties such as the refractive index reach the desired values.
[0162] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.
[0163] <Optical Instrument Embodiment>
[0164] The glass elements made from the above-mentioned glass element embodiments are optically designed to form optical components or optical assemblies using one or more glass elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, photolithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips, or in camera equipment and devices in the automotive field.
[0165] Figure 1 is the thermal expansion coefficient (α) of the optical glass embodiment 10 within the range of 100 to 300°C. 100~300℃ ) test results and their polynomial fitting curves. In the figure, the thermal expansion coefficient (α 100~300℃ ) has an average value of 62×10 -7 / ℃.
Claims
1. An optical glass, characterized in that: Its components, expressed in weight percentage, include: SiO2: 3-15%; B2O3: 24-34%; La2O3: 1-12%; Y2O3: 7-16%; ZnO: 20-30%; ZrO2: 3-9%; Nb2O5: 1-6%; Al2O3: 0-8%, among which (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) is 0.085-0.
375.
2. The optical glass according to claim 1, characterized in that: Its components, expressed in weight percentage, also contain: Gd2O3: 0-12%; and / or Li2O: 0-4%; and / or Na2O: 0-5%; and / or K2O: 0-5%; and / or MgO: 0-5%; and / or CaO: 0-5%; and / or SrO: 0-5%; and / or BaO: 0-4%; and / or Ta2O5: 0-5%; and / or WO3: 0-3%; and / or Sb2O3: 0-0.5%.
3. An optical glass, characterized in that: Its components contain SiO2, B2O3, La2O3, Y2O3, ZnO, ZrO2 and Nb2O5 as essential components. Its components are expressed in weight percentage and contain 0-8% Al2O3, wherein (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) is 0.085-0.
375. The refractive index of the optical glass is n d is 1.70~1.75, Abbe number ν d 43~48, short wave relative partial dispersion ΔP g,F The thermal expansion coefficient α is below -0.0075. 100~300℃ 70×10 -7 / ℃ below.
4. The optical glass according to claim 3, characterized in that: Its components, expressed in weight percentage, contain: SiO2: 3-15%; and / or B2O3: 24-34%; and / or La2O3: 1-12%; and / or Y2O3: 7-16%; and / or ZnO: 20-30%; and / or ZrO2: 3-9%; and / or Nb2O5: 1-6%; and / or Gd2O3: 0-12%; and / or Li2O: 0-4%; and / or Na2O: 0-5%; and / or K2O: 0-5%; and / or MgO: 0-5%; and / or CaO: 0-5%; and / or SrO: 0-5%; and / or BaO: 0-4%; and / or Ta2O5: 0-5%; and / or WO3: 0-3%; and / or Sb2O3: 0-0.5%.
5. The optical glass according to any one of claims 1 to 4, characterized in that , whose components are expressed in weight percentage and meet one or more of the following 7 conditions: 1) Al2O3+B2O3+SiO2 is 35-45%, preferably Al2O3+B2O3+SiO2 is 36-44%, more preferably Al2O3+B2O3+SiO2 is 37-43%; 2) B2O3 / (SiO2+Al2O3) is 1.5 to 4.0, preferably B2O3 / (SiO2+Al2O3) is 1.6 to 3.8, and more preferably B2O3 / (SiO2+Al2O3) is 1.8 to 3.6; 3) (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) is 0.100 to 0.325, preferably (Al2O3+ZrO2) / (Al2O3+B2O3+SiO2) is 0.125-0.300; 4) Y2O3 / (2×ZnO+B2O3) is 0.090 to 0.210, preferably Y2O3 / (2×ZnO+B2O3) is 0.110 to 0.205, and more preferably Y2O3 / (2×ZnO+B2O3) is 0.130 to 0.200; 5) Gd2O3+Y2O3 is 13-22%, preferably Gd2O3+Y2O3 is 14-21%, and more preferably Gd2O3+Y2O3 is 15-20%; 6) (2×Li2O+SiO2) / ZrO2 is 0.800 to 5.0, preferably (2×Li2O+SiO2) / ZrO2 is 0.850 to 4.5, and more preferably (2×Li2O+SiO2) / ZrO2 is 0.900 to 4.0; 7) (Nb2O5+Ta2O5+WO3) / (La2O3+ZrO2) is 0.05 to 0.65, preferably (Nb2O5+Ta2O5+WO3) / (La2O3+ZrO2) is 0.05 to 0.55, and more preferably (Nb2O5+Ta2O5+WO3) / (La2O3+ZrO2) is 0.05~0.
45.
6. The optical glass according to any one of claims 1 to 4, characterized in that , the components are expressed in weight percentage, containing: SiO2: 4-14%, preferably SiO2: 5-13%; and / or B2O3: 25-33%, preferably B2O3: 26-32%; and / or La2O3: 2-10%, preferably La2O3: 3-8%; and / or Y2O3: 8-15%, preferably Y2O3: 9-14%; and / or ZnO: 21-28%, preferably ZnO: 22-26%; and / or ZrO2: 3.5-8.5%, preferably ZrO2: 4-8%; and / or Nb2O5: 1.5-5.5%, preferably Nb2O5: 2-5%; and / or Al2O3: 0.5-6%, preferably Al2O 3: 1-4%; and / or Gd2O3: 0.5-9%, preferably Gd2O3: 1-6%; and / or Li2O: 0.05-3%, preferably Li2O: 0.1-2%; and / or Na2O: 0-3%, preferably Na2O: 0-1%; and / or K2O: 0-2%; and / or MgO: 0-2%; and / or CaO: 0-2%; and / or SrO: 0-2%; and / or BaO: 0-3%, preferably BaO: 0-2%; and / or Ta2O5: 0-2%; and / or WO3: 0-1.5%, preferably WO3: 0.1-1%; and / or Sb2O3: 0-0.3%, preferably Sb2O3: 0-0.2%.
7. The optical glass according to any one of claims 1 to 4, characterized in that , the optical glass does not contain K2O; and / or does not contain MgO; and / or does not contain CaO; and / or does not contain SrO; and / or does not contain Ta2O5; and / or does not contain Bi2O3; and / or does not contain TiO2; and / or does not contain P2O5; and / or does not contain GeO2; and / or does not contain TeO2; and / or does not contain Tl2O; and / or does not contain CdO; and / or does not contain As2O3; and / or does not contain PbO; and / or does not contain Cl - ; and / or does not contain F - ; and / or does not contain S 2- .
8. The optical glass according to any one of claims 1 to 4, characterized in that , the refractive index n of the optical glass d 1.70 to 1.75, preferably 1.71 to 1.74; Abbe number ν d It is 43 to 48, preferably 44 to 47.
5.
9. The optical glass according to any one of claims 1 to 4, characterized in that , the short-wave partial dispersion P of the optical glass g,F is less than 0.5600, preferably less than 0.5590, more preferably less than 0.5580; short-wave relative partial dispersion ΔP g,F It is -0.0075 or less, preferably -0.0080 or less, and more preferably -0.0085 or less.
10. The optical glass according to any one of claims 1 to 4, characterized in that , the λ of the optical glass 80 is 370nm or less, preferably 365nm or less, more preferably 360nm or less; and / or λ5 is 330nm or less, preferably 325nm or less, more preferably 320nm or less; and / or water resistance stability R W Class 1 and the water leaching resistance percentage is less than 0.04%, preferably Class 1 and the water leaching resistance percentage is below 0.03%, more preferably Class 1 and the water leaching resistance percentage is below 0.02%; and / or acid resistance stability R A 4 or more, preferably 3 or more; and / or density ρ is 4.05 g / cm 3 Below, preferably 4.00 g / cm 3 Below, more preferably 3.95g / cm 3 Below; and / or thermal expansion coefficient α -30~70℃ 60×10 -7 / ℃ or less, preferably 58×10 -7 / °C or less, more preferably 56×10 -7 / ℃ or below; and / or thermal expansion coefficient α 100~300℃ 70×10 -7 / ℃ or less, preferably 67×10 -7 / °C or less, more preferably 64×10 -7 / ℃ or below; and / or micro Vickers hardness H v 670×10 7 Pa or more, preferably 690×10 7 Pa or more, more preferably 710×10 7 Pa or above; and / or transition temperature T g The temperature is 540-630°C, preferably 550-620°C, more preferably 560-610°C; and / or the anti-thermal forming crystallization performance is 3 or more, preferably 2 or more, more preferably 1; and / or the anti-crystallization performance is 3 or more, preferably 2 or more; and / or the bubble degree is A0 or more, preferably A 00 and / or a refining temperature of 1260°C or less, preferably 1240°C or less, more preferably 1220°C or less.
11. A glass preform, characterized in that , made of the optical glass described in any one of claims 1 to 10.
12. An optical element, characterized in that , made of the optical glass described in any one of claims 1 to 10 or the glass preform described in claim 11.
13. An optical instrument, characterized in that , containing the optical glass according to any one of claims 1 to 10, or containing the optical element according to claim 12.